Effects of supplementation with L. purpureus, graded levels of L. pallida 14203 or S. sesban 1198 on feed intake and live weight gain of Menz sheep - Melaku, S.; Peters, Kurt J.; Tegegne, Azage (Ethiopian Society of Animal Production, 2003)
The research was conducted at the International Livestock Research Institute's (ILRI) Debre Zeit research station situated in the central highlands of Ethiopia at 38° 58' E. 80 44' N. The multipurpose tree (MPTs) leaves and L. purpureus were harvested and dried in a shade at the research station. Seventy individually penned Menz ewes with a mean initial weight of 14.77 f 0.32 kg (mean t SD) were supplemented with L. pallida 14203, S. sesban 1198 at 0.9 °%, 1.2 % and 1. 5 % of live weight for a feeding period of 5 months. L. purpureus, supplemented at 1.2 % of live weight was used as a control. The basal feed, chopped tef straw, mineral blocks and water were offered ad libitum. The experimental design was a randomized block design. Sheep were weighed fortnightly. Content of crude protein (CP) was lower and that of fiber was higher in L. purpureus compared to both MPTs. Soluble phenolics and condensed tannins were highest in L. pallida 14203, followed by S. sesban 1198 and least in L. purpureus. At equal levels of offer, DCP intake was significantly lower (P < 0.001) in sheep supplemented with L. pallida 14203 than those supplemented with S. sesban 1198 or L. purpureus. L. pallida 14203 was readily consumed, whereas animals on L. purpureus and higher levels of S. sesban 1198 did not totally consume offered supplement feed. Daily live weight gain was significantly higher in S. sesban 1198 supplemented than in L. pallida 14203 (P < 0.05) or L. purpureus (P < 0.01) supplemented animals.